1957
DOI: 10.1111/j.1550-7408.1957.tb02489.x
|View full text |Cite
|
Sign up to set email alerts
|

Volume Expansion of Euglena gracilis in Fresh Culture Media*

Abstract: SUMMARY. Transfers of Euglena gracilis to fresh media gave rise to increased volumes of the flagellates, the magnitude of expansion varying with temperature, pH, osmotic pressure, and number of nutritional particles in the medium. Expansion was accompanied by decreased protoplasmic density and increased intracellular solids and water. When the population density of the flagellates was more than optimal, competition for substrates was reflected in reduced maximum volume. Below the optimal range, a similar decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1958
1958
1975
1975

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Corbett ( 2 ) found that volume changes in Euglena gracilis were correlated with temperature, osmotic pressure, and most importantly for the purposes here, with the density of Euglena. Maximum size was reached at densities between 100 and 1000 organisms/ml.…”
Section: In Amoeba Proteus and Didinium Nasutum The Number Ofmentioning
confidence: 68%
See 1 more Smart Citation
“…Corbett ( 2 ) found that volume changes in Euglena gracilis were correlated with temperature, osmotic pressure, and most importantly for the purposes here, with the density of Euglena. Maximum size was reached at densities between 100 and 1000 organisms/ml.…”
Section: In Amoeba Proteus and Didinium Nasutum The Number Ofmentioning
confidence: 68%
“…The stepwise increase of the numbers of didinia indicates that they divided synchronously throughout the course of the experiments (Figs. [2][3][4][5]. Consequently, there is a regular oscillation in mean size, a maximum occurring just before division and a minimum just after.…”
Section: Resultsmentioning
confidence: 99%